The Relationship Between Isolation and Self-Concept in The Elementary School Classroom: An Exploratory Study - Rudner, Howard L.; Markoff, Morrie W. (Canadian Journal of Counselling and Psychotherapy, 2012)
In this study the relationship between isolation in the elementary school classroom and self-concept was investigated. It was hypothesized that children who were isolated or rejected by their classmates would possess low self-concepts. No such relationship was found. The design of the sociometric instrument used to identify the isolate generated more questions than it answered. Also discussed is the instrument chosen to measure the level of self-concept of an elementary school child. One significant finding of this study was that the self-concepts of suburban children differed from those found in the rural sample.